Social Security through Guaranteed Employment. (November 2015) - Fraser, Neil
Abstract This article reviews the Mahatma Gandhi National Rural Employment Guarantee Scheme (NREGA), perhaps India's foremost social security scheme, which is in the form of a right for rural households throughout India to work for up to 100 days a year in public works and to be paid the minimum wage for unskilled labourers. It is argued that self‐targeting leads to a more pro‐poor scheme than a cash transfer programme. However, in many states, especially poor states, work for NREGA is shown to be not a right. This is a major aspect of the corruption which gives the scheme a bad name. Also generally disappointing is the value of the assets created by the public works. But it is argued that NREGA is worth salvaging, especially if the example of the best states could be followed more widely. Attention is particularly drawn to the contribution of NREGA to the empowerment of women and scheduled castes and tribes in much of rural India.